The Evolution of Swimming Science Research: Content analysis of the “Biomechanics and Medicine in Swimming” Proceedings Book from 1971 to 2006. - Barbosa, Tiago (2016)
The aim of this study was to analyze the evolution of the swimming science research based on the content analysis of the “Biomechanics and Medicine in Swimming” Proceeding books series from 1971 to 2006. It was evaluated the content of all the 622 papers published in the Proceedings books of the Symposiums of Biomechanics and Medicine in Swimming. It was defined two main categories: (i) The “Aquatic activity” studied in each paper analyzed (included the sub-categories Competitive swimming, Water Polo, Synchronized Swimming, Diving, Hydrotherapy, Infant Swim, Head-out Aquatic Exercises, Fin Swimming and others) and; (ii) The main “scientific area” (including the sub-categories Biomechanics, Psychology, Sociology, Pedagogy/Teaching, Biochemistry, Physiology, Thermoregulation, Hydrodynamics, Electromyography, Anthropometry, Equipments/Methodologies, Clinical Medicine/Traumatology and Interdisciplinary assessment) applied for the assessment. There was an increasing number of papers published within the period of time analyzed (ranging from 23 papers in 1971 to 145 manuscripts in 2006). Comparing the sub-categories related to “Aquatic activity” the one with more research done was clearly the “competitive swimming” (ranging from 78.8 % in 1971 to 100 % in 1996). In the last decade there is a slight but increasing interest in “head-out aquatic exercises” (e.g., being the second most studied aquatic activity in 2006 with 6.9%). Analyzing the main “scientific area” of study, “Biomechanics” was the area of assessment most often (ranging from 27.3 % in 1988 to 60 % in 1979), followed by the “Physiology”. Since 2003 it is verified an increasing trend in “interdisciplinary assessment” manuscripts (e.g., 9.7 % in 2003 and 21.4 % in 2006, shifting from the third to second area of interest).